Residential noise from nearby oil and gas well construction and drilling. (November 2018) - Blair, Benjamin; Brindley, Stephen; Dinkeloo, Eero; McKenzie, Lisa; Adgate, John
Abstract Public concern about oil and gas (O&G) operations in residential areas is substantial. Noise from construction and drilling related to O&G operations may be greater than other phases of O&G operations; yet the impacts of audible and low-frequency noise during these operations are not extensively explored nor the effects on health well understood. This study documents the noise levels at a multi-well O&G well pad during construction and drilling in a residential area in Colorado. A-weighted (dBA) and C-weighted (dBC) noise measurements were collected at four locations during development over a 3-month period. The maximum 1-min equivalent continuous sound levels over a 1-month period were 60.2 dBA and 80.0 dBC. Overall, 41.1% of daytime and 23.6% of nighttime dBA 1-min equivalent continuous noise measurements were found to exceed 50 dBA, and 97.5% of daytime and 98.3% of nighttime measurements were found to exceed 60 dBC. Noise levels exceeding 50 dBA or 60 dBC may cause annoyance and be detrimental to health; thus, these noise levels have the potential to impact health and noise levels and associated health effects warrant further investigation.